Resonant effects in the strongly driven phase-biased Cooper-pair box
We study the time-averaged upper level occupation probability in a strongly driven two-level system, particularly its dependence on the driving amplitude x0 and frequency w and the energy level separation DE. In contrast to the case of weak driving (x0